2019
DOI: 10.26603/ijspt20190376
|View full text |Cite
|
Sign up to set email alerts
|

Medial and Lateral Hamstrings Response and Force Production at Varying Degrees of Knee Flexion and Tibial Rotation in Healthy Individuals

Abstract: Background:Hamstring weakness is a contributor to lower extremity pathology. Influence of knee flexion and tibial rotation on hamstrings muscle activation and knee flexion force has not been documented in the literature. Hypothesis/Purpose:The purpose of the study was to determine the angle of knee flexion and tibial rotation that elicits the greatest knee flexion force and hamstrings activation in healthy, physically active adults. Study Design: Descriptive, observational cohort studyMethods: Eighteen young h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(52 reference statements)
3
12
0
Order By: Relevance
“…Meanwhile, force and torque were significantly reduced in IR compared with those in both NR and ER, with no significant difference between NR and ER. This was consistent with a previous study, which showed a significant decrease in peak force output (21). Although EMG activity and force seem inconsistent with each other in this study, EMG activity was also partially diminished in IR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, force and torque were significantly reduced in IR compared with those in both NR and ER, with no significant difference between NR and ER. This was consistent with a previous study, which showed a significant decrease in peak force output (21). Although EMG activity and force seem inconsistent with each other in this study, EMG activity was also partially diminished in IR.…”
Section: Discussionsupporting
confidence: 89%
“…MH versus LH activation ratio was significantly lesser in ER than IR, but there was no difference in the ratio in men and women when analyzed separately. A recent study by Beyer also showed a decrease in MH activity in IR and ER, and no significant difference in LH at 60° knee flexion (21). In the present study, in which maximal isometric contraction was applied, the EMG activities of all three muscles were significantly diminished in ER and IR compared with those in NR.…”
Section: Discussionsupporting
confidence: 56%
“…The biceps femoris EMG amplitude is likely reduced during the leg press to allow for simultaneous knee-and hip extension, as previously postulated for the semimembranosus and semimembranosus (Fujiwara and Basmajian, 1975;Yamashita, 1988). Moreover, higher biceps femoris activation has been observed in near full knee extension compared to smaller knee angles during isometric knee flexion (Beyer et al, 2019). While a 170° knee joint angle was only reached near the top position during the leg press, the knee was in a constant 170° angle throughout the movement during the kickback, allowing for a longer duration in the position allowing for the highest EMG amplitude.…”
Section: Discussionsupporting
confidence: 56%
“…Information regarding the effects of knee joint angle on hamstrings activity during knee flexion contractions varies between studies [ 79 , 127 , 128 , 149 151 , 158 ] (Table 3 ). In particular, BFlh EMG amplitude, measured using bipolar surface or intramuscular electrodes approximately in the middle of the muscle belly, has been reported to increase [ 79 , 128 , 132 , 137 , 150 , 151 , 154 ], decrease [ 149 , 156 , 158 , 161 ], increase and then decrease [ 130 , 157 , 159 ] or remain unaltered [ 127 , 152 , 155 ] as the knee approaches full extension (longer muscle length). Similarly, ST EMG amplitude has been reported to increase [ 137 , 155 ], decrease [ 128 , 132 , 149 ], increase and then decrease [ 165 ], or remain unaltered [ 79 , 127 , 151 , 154 ] as the knee extends, and SM EMG signal amplitude was found to increase [ 79 , 132 , 155 ], decrease [ 128 , 149 ], increase and then decrease [ 157 ], or remain unaltered [ 127 , 151 , 158 ] from flexion to full extension.…”
Section: Main Textmentioning
confidence: 99%